Homogeneous polymer/filler composite membrane by spraying method for enhanced direct methanol fuel cell performance. (2nd August 2018) - Prapainainar, Paweena; Maliwan, Sumanut; Sarakham, Kannikar; Du, Zehui; Prapainainar, Chaiwat; Holmes, Stuart M.; Kongkachuichay, Paisan
Abstract: In this work, composite membranes for a direct methanol fuel cell (DMFC) were prepared using a spraying method to improve cell performance especially at a high methanol concentration. Nafion polymer and mordenite as a filler were used for the composite membrane preparation using a spraying method and a conventional solution casting method and the membranes from the two methods were compared. SEM images showed that a more homogeneous composite membrane could be obtained using the spraying method. The effect of mordenite content was also studied. The membranes were consequently characterized and tested in DMFC operation. The results were compared to those prepared using the solution casting method at 30, 50, and 70 °C with methanol concentrations of 2, 4, and 8 M. It was found that the membrane with 5 wt.% mordenite from the spraying method showed a vast improvement in DMFC performance. When the cell was operated at 70 °C, the maximum power density of 5 wt.% mordenite from the spraying method was higher than that of commercial membrane and 5 wt.% from the solution casting method. Power densities from the 5 wt.% sprayed membrane were higher by around 29%, 40%, and 60% at 2, 4, and 8 M methanol concentration, respectively. Graphical abstract: Image 1 Highlights: Membranes from spraying and solution casting methods were compared. Homogeneous composite membranes were successfully fabricated by spraying method. The 5 wt.% mordenite sprayed membrane improved DMFC performances.